Transformation of Contemporary Islamic Justice: Integration of Juridical Norms and Socio-Cultural Traditions in Indonesia - Anwar Pahutar, Agus; Hifzhi Siregar, Neila; Sa, Saifullah; Asmaret, Desi; Kamal, Tamrin (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2025)
The transformation of Islamic justice in Indonesia reflects the dynamics between formal juridical norms and the socio-cultural realities of diverse societies. Religious Courts, as part of the national legal system, do not solely implement Islamic law in a normative form, but must also interact and negotiate with local values, social structures, and broader political and legal configurations. This research critically examines how the integration between Islamic legal norms and socio-cultural traditions occurs in judicial practice, as well as how these interactions affect the effectiveness and legitimacy of Islamic judicial institutions in Indonesia. The juridical-sociological approach is used to explore the relationship between legal norms and the context of society (living law), with an emphasis on aspects of social acceptance and substantive justice. The findings of the study show that although institutionally the Religious Courts have been strengthened, there is still tension between the spirit of codification of sharia law and the flexibility of local culture. In this context, the transformation of Islamic justice is not only a matter of legal reform, but also involves the repositioning of the role of religion, the state, and society in formulating and enforcing contextual justice. Thus, there is a need to strengthen an integrative paradigm in the reform of Islamic law that is able to bridge juridical norms with social reality, in order to strengthen the responsiveness and legitimacy of Islamic justice in the midst of the plurality of laws in Indonesia.